PENGARUH MOTIVASI KERJA, KEPEMIMPINAN, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. INDORAMA PETROCHEMICALS KOTA CILEGON - Alya Rahma Zatining Ngasti; Eloh Bahiroh (Universitas Nusa Cendana, 2023)
This research aims to find out the effect of Motivation, Leadership, and Work Discipline on Employee Performance at PT. Indorama Petrochemicals Cilegon. The sample of this study is 73 respondents using random sampling techniques. The data analysis technique is Structural Equation Modelling (SEM) using the SmartPLS 3.0 analysis tool. The results of this study show that Motivation has a positive and significant effect on Employee Performance, Leadership has a negative and not significant effect on Employee Performance, and Work Discipline has a positive and significant effect on Employee Performance. Keywords: Work Motivation; Leadership; Work Discipline; Employee Performance